The effect of choice options in training curricula on the supply of and demand for apprenticeships - Jansen, Anika [Verfasser]; De Grip, Andries [Verfasser]; Kriechel, Ben [Verfasser] (My University, 2016)
"Building on Lazear's skill weights approach, we study the effect of having more or less heterogeneity in the training curriculum on supply of and demand for apprenticeship training. Modernizations of training curricula provide us with a quasi-experimental setting as these modernizations can be seen as a relatively exogenous shock. We argue that firms will train more apprentices when they have more choice options in the training curriculum because of (1) the higher productivity of graduates who have acquired more skills that are relevant for the firm and (2) firms' higher market power in the wage bargaining process with graduates. We test this hypothesis on data on the supply of apprenticeship places in Germany in all occupations from 2004 to 2014. We find that a more heterogeneous curriculum increases both firms' supply of and students' demand for training places." (Authors' abstract, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 2.2.2.1 Ausbildungsordnungen; G 1.3.1.1 Ausbildungsstellenmarkt; Betriebliche Berufsausbildung; Ausbildungsordnung; Berufsstruktur; Monoberuf; Spezialisierung; Wahlqualifikation; Zusatzqualifikation; Einflussfaktor; Ausbildungsplatzangebot; Ausbildungsplatznachfrage